Security System for IoT Applications Based on Hybrid Fuzzy Possibility C-Means Clustering - Parmar, Monika; Kaur, Navneet; Tripathy, Ramamani; Singh, Hakam; Gupta, Lipika (2024 International Conference on Integrated Circuits, Communication, and Computing Systems (ICIC3S), 2024)
With improved applications in a variety of industries, the Internet of Things (IoT) and distributed ledger innovation are captivating services and industrial advancements. The IoT and blockchain industries are expected to grow by a factor of three by 2025. As computational power increases, many IoT applications confront substantial challenges with regard to data security and scalability. Additionally, Proof-of-work suffers from a number of problems that make it impractical for IoT applications, therefore Practical Byzantine Fault Tolerance (PBFT) is a widely utilized type of decentralized agreement. Nevertheless, the network node's trust in PBFT is not assured, and the approach to achieving consensus consumes a substantial quantity of network resources. This research proposes a new consensus mechanism known as a Hybrid consensus blockchain algorithm. This includes the features that provide safety into the clustering algorithm for identifying and classifying attackers. To promote cluster diversity in wireless ad hoc networks, a technique called Hybrid fuzzy Possibility C Means Clustering (HFPCM) is developed. For detecting and organizing the intruders in order to create the organization more attack resilient, a Byzantine agreement based cooperative methodology is used.